The Effect of Digital Financial Inclusion and Financial Literacy on MSME Performance Study on Kapanewon Dlingo MSMEs - Hidayati, Nur; Yacobus, Aryono (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The aim of this research is to examine the effect of digital financial inclusion on the performance of MSMEs in the Kapanewon Dlingo area and to test the effect of financial literacy on the performance of MSMEs in the Kapanewon Dlingo area. The phenomenon in this research is related to MSME actors in the Kapnewon Dlingo area. This research includes quantitative or statistical research carried out to test hypotheses. This research uses two types of data, namely primary data and secondary data. The population in this study was 736 MSMEs recorded in the Kapanewon Dlingo Prosperity Bureau. The sampling technique used purposive sampling with a sample of 238 Kapanewon Dlingo MSMEs. The analysis technique in this research uses descriptive analysis techniques and partial analysis or t-test with the help of the SPSS version 25 program. The results of this research show that 1) digital financial inclusion has a significant effect on the performance of Kapanewon Dlingo MSMEs, 2) Financial literacy has a significant effect on the performance of Kapanewon Dlingo MSMEs.